Korelasi Pengetahuan Gizi dan Status Gizi pada Siswa Kelas 1 di SD Muhammadiyah 1 Kota Malang - Nurhayati, Aprinia Dian; Zanieqah, Dzata Ziek; Silvia, Rizka (PHARMADEMICA : Jurnal Kefarmasian dan Gizi, 2025)
Nutritional status in schoolchildren is known to affect their concentration in learning, cognitive abilities, growth, development, and immune system. Nutritional knowledge is one of the factors known to influence the nutritional status of schoolchildren. However, research that analyzes the correlation between the nutritional knowledge of students who are just starting elementary school and their nutritional status is still limited. This study intends to analyze the correlation between nutritional knowledge and nutritional status in first-grade students at SD Muhammadiyah 1, Malang City, East Java. This was an observational study with a cross-sectional approach, conducted in July 2025. The study involved first-grade students at SD Muhammadiyah 1, Malang City. Ethical approval with number 01.07.09/UN32.14.2.8/LT/2025 was obtained from the Ethics Committee of Universitas Negeri Malang. Data on nutritional knowledge were obtained from interviews using a student knowledge questionnaire. Data on the students' nutritional status were obtained from the average results of weight (W) and height (H) measurements, which were processed into BMI-for-age (body mass index for age) data. The results showed no statistically significant correlation between nutritional knowledge and the nutritional status of first-grade students at SD Muhammadiyah 1, Malang City (correlation coefficient of 0.071 with p>0.05). Other factors, such as parental habits, environment, and access to food, may be more influential on children's eating practices than nutritional knowledge.